Accelerating Creative Techno-preneuriship Through Innovative Design and Technology Integration - Zulkarnaen Khidzir, Nik; Mat Daud, Khairul Azhar; Hamid, Hidayat (KnE Social Sciences, 2023)
Creative techno-preneurship investigates a new frontier in the integration of creative technology to design more innovative entrepreneurship models to suit their business model and the goals of their organization. Entrepreneurs use this technology and approach creatively to identify opportunities from advanced creative technology research and development that can be used for entrepreneurship activities. To remain competitive, businesses must innovate. Simultaneously, technology is constantly advancing, and work-related tools are constantly changing. This forces organizations to stay current with technology and puts pressure on employees to use the technologies at their disposal to create innovative solutions that further the organization’s goals. It is hoped that this integration model will be a milestone in the trend to support future developments of digital content in particular to uplift the digital comic development in Malaysia. Keywords: creative innovation, digital technology, creative techno-preneurship, incubator